The Influence of Intellectual, Emotional, Spiritual and Social Intelligence on Students' Morals in Integrated Islamic Junior High School in Batam City - Heri Suprapto; Zamsiswaya Zamsiswaya; Asmal May (Dinasti Publisher, 2025)
This study aims to analyze the influence of intellectual, emotional, spiritual, and social intelligence on the morals of students in Integrated Islamic Junior High Schools throughout Batam City. The research method uses a quantitative approach with data collection techniques in the form of questionnaires, interviews and documentation. The research sample consisted of a number of students randomly selected from several Integrated Islamic Junior High Schools in Batam City. The results of this study First, there is no significant influence of intellectual intelligence on the morals of students in Integrated Islamic Junior High Schools throughout Batam City, this is evidenced by the calculation of product moment with a Sig. (2-tailed) value of 0.108 (0.108> 0.05). Second, there is no significant influence of emotional intelligence on the morals of students in Integrated Islamic Junior High Schools throughout Batam City, this is evidenced by the calculation of product moment with a sig. 2 tailed product moment is 0.152 (0.152 > 0.05. Third, There is a significant influence of spiritual intelligence on students' morals in Integrated Islamic Junior High Schools throughout Batam City, this is proven by the calculation of product moment with a sig. 2 tailed product moment value of 0.025 (0.025 < 0.05). The magnitude of the influence of the spiritual intelligence variable is 31.6% and the remaining 68.4% is influenced by other variables. Fourth, There is no significant influence of social intelligence on students' morals in Integrated Islamic Junior High Schools throughout Batam City, this is proven by the calculation of product moment with a sig. 2 tailed product moment value of 0.152 (0.152 > 0.05).